Analisis Penguran Kerja Dalamproduktifitas Karyawan ( Study Kasus Pada CV Tunas Sari Bogor) - Cattleya, Cattleya; Suardy, Weman (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2003)
Planning is a firm has a share determine the ways a working direction of the firmâs activity. Thus and so, we know standard which needed in many kinds of activities conducted by the firm. By means of the firms planning we are able to se productivity and efficiency level of workers. Hence it could be made decision about facilities, workerâs requirement, cost and price of product exactly, besides it could be made measuring instrument as controller in operational activities of the firm